Simulation of CO Preferential Oxidation (COPrOx) Monolithic Reactors - Jeifetz, Leandro G. (2014)
In this work, a COPrOx monolithic reactor with a CuO/CeO2/Al2O3 catalytic washcoat was modelled to purify a H2 stream for a 2 kW PEM fuel cell. Preliminary simulations included isothermal monoliths operating between 423 and 463 K, and the optimization of linear axial temperature profiles. For a fixed total system size and a desired CO outlet molar fraction lower than 20 ppm, an isothermal temperature profile maximized the global selectivity towards CO oxidation. Then, different schemes of adiabatic monoliths with interstage cooling were modelled and evaluated. It was found that wide operating temperature ranges lower the necessary number of stages, but decrease the global selectivity and rise system sensitivity to inlet temperatures. A 1D heterogeneous model was used to simulate the monoliths.